The Effect of Capital Intensity, Corporate Social Responsibility, and Profitability on Tax Avoidance (In Manufacturing Companies Industry of Food & Beverage Sub Sectors Listed on Indonesia Stock Exchange 2015-2020) - Muhammad Irfan Aryatama; Surya Raharja (Diponegoro Journal of Accounting, 2021)
The main objective of this study is to determine the relationship between the variables of capital intensity, corporate social responsibility, and profitability on tax avoidance by manufacturing companies in the food & beverage sub-sector listed on the Indonesia Stock Exchange 2015-2020. This study has an overall sample of 96 food & beverage industry manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2020 period with predetermined criteria. The sample was selected using purposive sampling method and the analysis technique used panel data regression with the Eviews-9 program. The independent variables of this study are capital intensity, corporate social responsibility, and profitability using ROA measurement. While the dependent variable in this study is tax avoidance which is measured using ETR. The results of this study indicate that several variables of capital intensity have a positive effect on tax avoidance. Corporate social responsibility has a negative effect on tax avoidance. Then, Return on Assets, as a proxy for measuring profitability, has no significant effect on tax avoidance.